Pengaruh Desain Kemasan dan Ecommerce Terhadap Keputusan Pembelian Jamu Herbal dan Rempah Madura - Ibnu Sholah; Yudhi Prasetya Mada (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The use of biopharmaceutical plants as traditional medicine in Madura has been going on for quite a long time, because medicinal plants and spices as raw materials for the traditional medicine industry are available in quite a lot in four districts in Madura. Traditional medicine SMEs have made many innovations to attract customers, one of which is by making packaging designs. In addition to innovation in terms of packaging design, the use of the internet is carried out to market Madura herbal herbal products. This method is called E-commerce. Data collection uses primary data and secondary data.